Analysis of Geometry Verification of X, Y, Z Correction Values with Megavoltage Computed Tomography Using Lower Extremity Positioning System in Prostate Cancer - Nursama Heru Apriantoro; Prabaningtyas Widya Dewi; Hamdi Rubiyanto (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2023)
The immobilization tool is used to minimize the movement caused while doing irradiation, one of the immobilization tools is the Lower Extremity Positioning System (LEPS) which is used to minimize movement in the Pelvis area. This research was conducted at Dr. Cipto Mangunkusumo Central General Hospital. The type of this research is analytics quantitative. This research used 15 samples with secondary data, which were selected based on inclusion and exclusion criteria’s. The secondary data will be analyzed namely the consistency between the Set-Up value (Couch Position before verification) and the MVCT (Couch Position after verification) value using the Non-Parametric Wilcoxon statistical test, and evaluating the shifting values of X, Y and Z with tolerance standards from AAPM TG-148 which is 2 mm. The results obtained are based on statistical analysis of the Set-Up value with the MVCT results obtained that there is no significant difference, and based on the overall substance, the total that exceeds the tolerance of X coordinates is 92 times with a percentage of 68%, from Y coordinates that is 80 times with a percentage of 59%, from the Z coordinate which is 51 times with a percentage of 38% there is a shift that exceeds tolerance. The conclusion is that the results of MVCT verification still occur that exceed the tolerance standard so that LEPS is still not effective in preventing shifts that occur during radiation therapy.